Reducing Employee Conflict through Islam Spirituality in Workplace "Analyzing Employee Performance In Islamic Banks" - Eka Pariyanti; Najmudin Najmudin (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
The research aims to empirically examine the effect of Employee Conflict through the workplace of Islamic spirituality and Analyze Employee performance at Islamic Banks. The data collection method uses a questionnaire. The total sample of 36 employees at the Islamic Bank in Indonesia. Data analysis techniques using linear regression and path path. The results showed that the Spiritual Workplace influenced the conflict of Islamic Bank employees. Conflict affects the performance of Islamic Bank employees. Spiritual Islamic Workplace affects the performance of Islamic Bank employees. Indirectly employee conflict through Islamic Workplace employees has a significant effect on the performance of Islamic Bank employees. The results of the study are expected to be an input for managers to reduce conflicts in the company with Islamic spirituality workplaces.